Genetic analysis of type 5 capsular polysaccharide expression by Staphylococcus aureus. - Lee, J C (1994)
Capsules are produced by over 90% of Staphylococcus aureus strains, and approximately 25% of clinical isolates express type 5 capsular polysaccharide (CP5). We mutagenized the type 5 strain Reynolds with Tn918 to target genes involved in CP5 expression. From a capsule-deficient mutant, we cloned into a cosmid vector an approximately 26-kb EcoRI fragment containing the transposon insertion. In the absence of tetracycline selection, Tn918 was spontaneously excised, thereby resulting in a plasmid containing 9.4 kb of S. aureus DNA flanking the Tn918 insertion site. The 9.4-kb DNA fragment was used to screen a cosmid library prepared from the wild-type strain. Positive colonies were identified by colony hybridization, and a restriction map of one clone (pJCL19 with an approximately 34-kb insert) carrying the putative capsule gene region was constructed. Fragments of pJCL19 were used to probe genomic DNA digests from S. aureus strains of different capsular serotypes. Fragments on the ends of the cloned DNA hybridized to fragments of similar sizes in most of the strains examined. Blots hybridized to two fragments flanking the central region of the cloned DNA showed restriction fragment length polymorphism. A centrally located DNA fragment hybridized only to DNA from capsular types 2, 4, and 5. DNA from pJCL19 was subcloned to a shuttle vector for complementation studies. A 6.2-kb EcoRI-ClaI fragment complemented CP5 expression in a capsule-negative mutant derived by mutagenesis with ethyl methanesulfonate. These experiments provide the necessary groundwork for identifying genes involved in CP5 expression by S. aureus.